Multi-disciplinary Trends in Artificial Intelligence 6th International Workshop, MIWAI 2012, Ho Chi Minh City, Vietnam, December 26-28, 2012. Proceedings - Sombattheera, Chattrakul; Loi, Nguyen Kim.; Wankar, Rajeev; Quan, Tho.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the refereed proceedings of the 6th Multi-disciplinary International Workshop On Artificial Intelligence, MIWAI 2012, held in Ho Chi Minh City, Vietnam, in December 2012. The 29 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections in AI-GIS for climate change, computer vision, decision theory, e-commerce and AI, multiagent planning and learning, game theory, industrial applications of AI, multiagent systems and evolving intelligence, robotics and Web services.
An Approach for Tuning the Parametric Water Flow Algorithm Based on ANN -- Mining Frequent Common Families in Trees -- A Structure Based Approach for Mathematical Expression Retrieval -- Toward Composite Object Classification Using a Probabilistic Inference Engine -- Relocation Action Planning in Electric Vehicle Sharing Systems -- A Guide to Portfolio-Based Planning -- Color and Texture Image Segmentation -- Evolutionary Multi-objective Optimization Based Proportional Integral Controller Design for Induction Motor Drive -- A Multi-agent Scheduling Model for Maximizing Agent Satisfaction -- Enhancing Pixel Oriented Visualization by Merging Circle View and Circle Segment Visualization Techniques -- Time Series Prediction Using Motif Information -- A New Approach for Measuring Semantic Similarity in Ontology and Its Application in Information Retrieval -- Local Stereo Matching by Joining Shiftable Window and Non-parametric Transform -- A Comprehensive Analysis and Study in Intrusion Detection System Using k-NN Algorithm -- AI-Based Support for Experimentation in an Environmental Biotechnological Process -- Stereo Matching by Fusion of Local Methods and Spatial Weighted Window -- Efficient Handling of 2D Image Queries Using VPC+-tree -- Novel Granular Framework for Attribute Reduction in Incomplete Decision Systems -- Agent-Based Control System for Sustainable Wastewater Treatment Process -- Tuning the Optimization Parameter Set for Code Size -- Mining Weighted Frequent Sub-graphs with Weight and Support Affinities -- Simple Spatial Clustering Algorithm Based on R-tree -- Minimal Generalization for Conjunctive Queries -- Interruptibility and Its Negative Impact on Graph Exploration Missions by a Team of Robots -- Monte-Carlo Search for Snakes and Coils -- Algorithms for Filtration of Unordered Sets of Regression Rules -- Evaluation of Jamendo Database as Training Set for Automatic Genre Recognition -- An Integrated Model for Financial Data Mining -- Correlation Based Feature Selection Using Quantum Bio Inspired Estimation of Distribution Algorithm.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Database Management; Algorithm Analysis and Problem Complexity